2016
DOI: 10.17265/2159-5542/2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Attachment Styles, Emotion Regulation and Psychopathology Symptoms in Turkish and American Students

Abstract: Two samples of university students, one from Turkey and the other from the USA, were compared on measures of attachment styles, difficulties in emotional regulation and self-reported symptoms of psychopathology. Results indicated that for both samples the level of anxiety in attachment and the lack of strategies in emotional regulation predicted several symptoms of psychopathology. Differences emerged in demographic predictors with parents' educational level predicting many of the symptoms in the Turkish popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although the above results regarding the influence of difficulties in emotional regulation and attachment styles on violence were expected, given the evidence that had previously linked these variables to violence [41][42][43][44][45][46][47][61][62][63][64][65][66][67][68], the role of sexual orientation is noteworthy. In this regard, we can mention that, although violence in couple relationships can come from any person regardless their sexual orientation, recent studies focused on intimate partner relationships agree that heterosexual couples are characterized by a high prevalence of violence in both men and women [49][50][51].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Although the above results regarding the influence of difficulties in emotional regulation and attachment styles on violence were expected, given the evidence that had previously linked these variables to violence [41][42][43][44][45][46][47][61][62][63][64][65][66][67][68], the role of sexual orientation is noteworthy. In this regard, we can mention that, although violence in couple relationships can come from any person regardless their sexual orientation, recent studies focused on intimate partner relationships agree that heterosexual couples are characterized by a high prevalence of violence in both men and women [49][50][51].…”
Section: Discussionmentioning
confidence: 77%
“…These studies are consistent with our findings, which show a high prevalence of insecure attachment styles in subjects with emotional regulation difficulties. These facts seem to explain the connection found between difficulties in emotional regulation, violence and the presence of insecure attachment styles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Therefore, this combination of factors could translate into violent responses towards their partners when the aggressors feel that their attachment needs are not satisfied [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, its significance results from the dependence of CSBD and PPU symptoms on cultural factors (Bőthe et al, 2023). Not only are attachment (Keller, 2013;Rothbaum et al, 2000;van Ijzendoorn & Sagi-Schwartz, 2008) and emotion regulation abilities (Keller & Otto, 2009;Matsumoto et al, 2008) sensitive to cultural differences in socialization, but also relationships between attachment, emotion regulation, and psychopathological symptoms can differ in various cultural contexts (Vatan & Pellitteri, 2016;Wang et al, 2022).…”
Section: Present Studymentioning
confidence: 99%
“…Given that various investigations have shown that emotional regulation difficulties and high levels of attachment insecurity underlie various health problems (Hu et al, 2014), it is important to conduct research in the areas of emotion regulation and attachment. Moreover, maladaptive strategies in managing emotional arousal can negatively affect cognitive processes and behavior which can lead to the development of psychopathology (Vatan and Pellitteri, 2016). For example, a deficiency in emotion regulation strategies and an anxious attachment style can predict psychopathological symptoms and adaptive problems.…”
Section: Introductionmentioning
confidence: 99%